THE FLOUTING OF COOPERATIVE PRINCIPLE MAXIMS: IMPLICATIONS FOR TEACHING OF PRAGMATICS IN EFL CLASSROOM - Nugraha, Sidik Indra (Indonesian EFL Journal, 2017)
This research reports on the flouting of cooperative principle maxims in a comedy movie. The data were taken from conversational exchanges of a comedy movie entitled Meet the Parents, and were collected by transcribing the exchanges exposing humor occurred in the movie. The exchanges potentially flouting the maxims were analyzed in the light of Grice’s CP maxims, elaborated further in Thomas (1995), to look into the types of maxims flouted and the ways the maxims were flouted. The exchanges were then further analyzed as to find whether the types of verbal humor are particular to each maxim flout. The analysis revealed that the four types of maxims, i.e. Quantity, Quality, Relevance, and Manner, occurred to have been flouted so as to create humor. The Quality maxim was the most commonly flouted (55.6%), whereas the least commonly flouted was the Relevance maxim (6.3%). The speakers flouted the maxims in a number of different ways particular to each maxim. Moreover, the analysis found that maxim flouts were relevant to the types of verbal humor. Therefore, given the importance of pragmatic competence that the foreign language (FL) learners should acquire, it is suggested that pragmatics should be explicitly taught and integrated into the teaching of English.Keywords: pragmatic competence, the cooperative principle, conversational exchanges, maxim flout, verbal humor